Multifaceted determinants influencing South African smallholder farmers’ choices to access and utilize underutilized crops - Cele, Thobani; Mkhize, Xolile (Frontiers in Sustainable Food Systems, 2025)
Underutilized crops (UCs), referred to as neglected or orphan crops, play a crucial role in addressing food security, nutrition, and rural development. However, despite their nutritional, economic, and environmental benefits, their consumption remains low among smallholder farmers. This study investigates the socio-economic and perceptual factors influencing smallholder farmers’ decisions to consume UCs, focusing on taro roots (Colocasia esculenta) and sweet potatoes (Ipomoea batatas) in KwaZulu-Natal, South Africa. Using data from 300 smallholder farmers, the study applies Factor Analysis (FA) and a binary logistic regression model to identify key determinants of UC consumption. The FA revealed four main perception factors influencing farmers’ decisions: perception of production, taste, awareness, and availability of UCs. The binary logistic regression results showed that household size (p < 0.05), marital status (p < 0.01), and gender (p < 0.05) significantly influenced UC consumption. Notably, farmers’ positive perception of taste (p < 0.1) increased the likelihood of consumption, whereas a lack of awareness (p < 0.1) had a negative impact. However, contrary to initial expectations, receiving a government grant (p < 0.05) and off-farm income (p < 0.05) were negatively associated with UC consumption, indicating that financial stability does not necessarily translate into increased adoption. These findings suggest that raising awareness, addressing market constraints, and fostering positive perceptions of UCs are crucial for increasing their consumption. The study highlights the need for targeted interventions to improve UC accessibility and appeal, thereby supporting sustainable food security strategies in South Africa and other regions with similar demographics.